Training of Science Teachers for Early Childhood and Primary Grades in Kenya - John T. Ng'Asike (New Zealand Journal of Teachers' Work)
This paper analyses teacher training in science education in early childhood development and primary grades in Kenya. The paper argues that even though the Kenya Government emphasises science as a subject critical for technological advancement and for achieving Vision 2030, the training of science teachers in early childhood and primary colleges nationally triggers a lot of quality questions. The author visited primary teacher training colleges and early childhood development training institutions in Nairobi, Kiambu and Thika Counties and observed the training activities and resources for science education. The article questions science teachers’ adaptability in ensuring science instruction captures the diverse cultures of Kenya in science classrooms. The author raises methodological questions in science instruction as it appears that the tutors training teachers at the colleges did not directly undergo training at the universities in Kenya that prepare them to train primary level teachers.